Study on The Pedigrees of Three Cases of Whole-Arm Translocation in Hainan China and Literature Review: A Retrospective Study - Chen Yunchun; Lin Yao; Zhao Zhengmin; Huang Xuning; Kong Changying; Liang Chongnan (International Journal of Fertility and Sterility, 2024)
In this study, in order to promote chromosome abnormality carriers eugenics, three patients with adverse pregnancyhistories were examined by cytogenetics and their pedigrees further analyzed. In this retrospective study, approximatelyanticoagulant peripheral venous blood from the patients was collected for peripheral blood cell culture andchromosome analysis. Karyotypes were analyzed in the BEIONMED karyotype analysis system. The karyotypes ofthe three probands were all whole-arm translocations (WATs): case 1 (DatabaseNo.3591): 46, XY, t (7; 13) (p10; p10)dn, two years of marriage in which the spouse did not have pregnancy, with azoospermia; case 2 (Database No.3809):46, XY, t(12; 17) (p10; q10), three spontaneous abortions within three years of marriage; case 3 (Database No.4914)46, XX, t(2;6) (p10; q10) mat, 21ps+pat, a year of marriage without pregnancy. When the parents are carriers ofWAT, the family should be considered to have a high reproductive risk, increasing the risk of producing offspring withchromosomal abnormalities. Three kinds of human chromosomal aberration karyotypes were reported for the first timeproviding an important basis for studying the occurrence and clinical consultation of chromosomal diseases.